Real-Time Dissecting the Entry and Intracellular Dynamics of Single Reovirus Particle - Liu, Jia; Yu, Cong; Gui, Jian-Fang; Pang, Dai-Wen; Zhang, Qi-Ya (Frontiers in Microbiology, 2018)
Reoviruses are non-enveloped viruses with wide host range, can cause serious infections in animals, plants and microorganism, e.g., aquareovirus, which is capable of causing serious haemorrhagic in aquatic animals. To date, the entry process of aquareovirus infection remains obscure. Real-time single-virus tracking are effective tools for exploring the details in viral infection process, which are crucial for understanding the pathogenic mechanism. Here, we used quantum dots-based single particle tracking technology combined with biochemical assays and ultrastructural observation to reveal unobservable infection steps and map dynamic interactions between a reovirus, Scophthalmus maximus reovirus (SMReV), and its host cell in real time. The results showed that the single membrane-bound reovirus particle can enter into the cell within several seconds through nascent clathrin-caoted pits, and most of the particles could internalize into cytoplasm within 30 min post-infection. The specific inhibitors analysis also showed that entry of SMREV depended on clathrin-mediated endocytosis rather than cavolin-mediated endocytosis. The motion analysis of internalized single particle indicated that the reovirus initially experienced slow and directed motion in the actin-enriched cell periphery, while it underwent relatively faster and directed movement toward the cell interior, suggesting that transport of SMReV was dependent on the cytoskeleton. Further, dual-labeling of virus and cytoskeleton and inhibitor analysis both demonstrated that transport of internalized SMReV was firstly dependent on actin filaments at the cell periphery, and then on microtubules toward the cell interior. Then visualization of SMReV trafficking in the endosomes revealed that the internalized reovirus particles were sorted from early endosomes to late endosomes, then part of them were delivered to lysosome. This study for the first time revealed the entry pathway, intracellular dynamic and the infection fate of fish reovirus in host cell in real time and in situ, which provided new insights into the infection mechanism of non-enveloped viruses.